Sweeping gestures: Alberto Alonso and the revolutionary musical in Cuba. Issue 1 (1st March 2019) - Schwall, Elizabeth
This article examines Cuban choreographer Alberto Alonso and his dance contributions to Cuban musical theatre from the 1940s through the early 1960s. The analysis integrates the histories of Alonso's training, performance career and choreographic output with developments in Cuban musical theatre before and after the 1959 Cuban Revolution. In particular, it focuses on Alonso's 1964 ballet El Solar (The Slum), which became a 1965 musical film Un día en el solar (A Day in the Slum) and live musical Mi Solar (My Slum). I argue that Alonso subtly questioned officialdom with his musical choreography that showed revolutionary movements springing not from the state but from Cuban citizens of different racial backgrounds as they enacted the chores and delights of life. Moreover, Alonso's work challenged cultural hierarchies, which held so-called high art forms like ballet above popular dance, by emphasizing the endless creativity of Cubans moving through their everyday.